FAKTOR-FAKTOR PENYEBAB ANAK PUTUS SEKOLAH DASAR DI DESA BUKIT RAYA,KECAMATAN SINGINGI HILIR,KABUPATEN KUANTAN SINGINGI - Friska Yanti T; M. Razif " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this research is to know the factors of then student on elementory school in Bukit Raya village, Singingi Hilir sub - District Kuantan Singingi District. Method of the research is using Descriptive kuantitative with the total of the population is 110 of studente and 110 of parents, but the total 25 of sample is only student and 25 of parents by using sampling random. The collection of the data research is gotten by using observation, method, interview and documentation and technique of analzing is Descriptive quantitative. Based on the research, there are four factors to effect the child to get out of school espacially in Bukit Raya village elementary school, Singingi Hilir Sub District Kuantan Singingi District. The first factor is economie which consist of 40%, the second factor is envinsment consist of 20% , the third is indogeneus factor which consist of 28% . and the last is the motivation of the family which is caused by economic condition of their family.Keywords : Student on elementory school